How to be a person - Newman, Catherine, 1968- (Storey Publishing, 2020)
For the kid who leaves a wet towel wadded up on the floor or forgets to put a new roll on the toilet-paper thingy, humorous writer and etiquette columnist Catherine Newman has created the ultimate guidebook to becoming a person whom everyone will like being around more. Jam-packed with tips, tricks, and skills -- all illustrated in an irresistible graphic novel-style -- this book shows kids just how easy it is to free themselves from parental nagging and become more dependable -- and they'll like themselves better, too! They'll learn how to deal with dirty rooms, care for pets and cactuses, stick up for somebody, and fold a T-shirt. They'll even get a crash course on using the kitchen (including how to turn a 33-cent package of ramen into dinner) and a boot camp for lending a hand outside the house (mowing, shoveling, and fixing something loose has never been easier). This handbook to becoming beyond helpful promises that every kid can be a valued and valuable member of the grown-up world.